Understanding of long-term impact of traumatic brain injury (TBI) on survivors'life during recovery: a 24 month follow-up study. - Mohamed Ludin, Salizar (2019)
Introduction: Traumatic brain injury (TBI) is a major medical and socio-economic problem and is the leading cause of death in children and young adult. Most of the patients will be admitted in the intensive care unit (ICU) for critical illness therapy. Critical illness survivors have reported problems during recovery. Despite medical advances the survival rate after severe TBI, but survivors may face a lifetime disability. The impact and outcome for TBI survivors is of interest to patients and their families, also to clinicians needing to provide prognostic information and health care providers who bear the health costs. Studies concluded that subjects with moderate and severe TBI shows physical and functional improvement but remain with the cognitive and psycho-social problem throughout recovery. Despite all the issues, the impact of TBI on long term survivors in Malaysia is unknown. This study aims to explore the TBI survivors' outcome and their family members' needs during recovery and rehabilitation periods. Methodology: A cohort study design (survey & interview) was employed to investigate the outcome of ICU survivors with sTBI and their caregivers experience during recovery and rehabilitation periods. The samples were those sTBI survivors and caregivers discharge from Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang and Hospital Sultanah Nur Zahirah (HSNZ) Kuala Terengganu. Glasgow Outcome Scale Extended (GOSE) and Quality of life after brain injury (QOLIBRI) were used to obtain baseline data (before discharge), followed by at 3, 6 and 12-month discharge. Caregivers' needs and experience were assessed through individual interviews and focus group discussions. Following that, the Homebased care module (HBCM) model was developed based on the qualitative data (Grounded Theory). Statistical and qualitative analyses were done.